1983
DOI: 10.3171/jns.1983.59.6.0958
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical management of extradural hematomas in children

Abstract: With the advent of computerized tomography (CT), an increasing number of patients with only minimal neurological symptoms and no signs of brain herniation are found to harbor subacute or chronic extradural hematomas (EH's). The authors present the cases of 11 symptomatic but neurologically normal children with medium to large EH's managed by close observation. These EH's were discovered 4 hours to 6 days after injury; three were in the posterior fossa, seven over the frontoparietal convexity, and one in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
14

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 58 publications
0
90
0
14
Order By: Relevance
“…Fever was treated with intravenous Dexamethason whereas headache was alleviated by release of occluded drain. It is believe that when fibrinolytic activity takes place the expansion phase of the clot occurs causing some degree of fluctuation in intracranial volume and pressure, resulting headache [19]. Patients with re-bleeding complained of severe pulsatile headache and gradually neurological deterioration occurred leading to immediate conventional craniotomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fever was treated with intravenous Dexamethason whereas headache was alleviated by release of occluded drain. It is believe that when fibrinolytic activity takes place the expansion phase of the clot occurs causing some degree of fluctuation in intracranial volume and pressure, resulting headache [19]. Patients with re-bleeding complained of severe pulsatile headache and gradually neurological deterioration occurred leading to immediate conventional craniotomy.…”
Section: Resultsmentioning
confidence: 99%
“…Bullock et al reported that the resolution of hematoma took 3 -15 weeks in the conservative management [12]. During the conservative management the reabsorption phase is always accompanied with expansive phase of clot due to fibrinolytic activity and in some cases latter phase may be predominant [19]. The major drawback of conservative treatment is prolong inpatient close monitoring and always remains high chance of re-bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In infants, the dura is firmly attached to the skull, but the connection between extracranial tissues is loose and easily detachable. 9) Such loose connection may allow spontaneous drainage of EDH into the subgaleal space through a skull fracture despite the absence of a substantial pressure gradient. Whereas spontaneous drainage of EDH through the skull fracture was completed within 24 hours after head trauma in all the previously reported cases, 1,3,4,6-8,10,11) the hematoma in our case continued to drain for more than 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, skull fractures in infants tend to form a jagged line rather than a straight line, because of the pliability and unevenness of the cranial flat bones. 9) Our patient showed an omega-shaped fracture that might have acted as a``hinge'' to facilitate discharge into the subgaleal space without a high pressure gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic epidural hematomas which are minimally symptomatic do not require surgical intervention. Despite the well performed clinical studies and the experience of many neurosurgeons using prompt evacuation of EDH, there have been number of reports suggesting nonoperative management of selective EDH [11][12][13][14][15][16][17][18]. The use of CT scan in head trauma revealed a new class of EDH patients who may be treated conservatively.…”
Section: Conservative Managementmentioning
confidence: 99%